2021
DOI: 10.1186/s12906-021-03469-x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine alleviates podocyte injury via calcium-dependent calpain-1 signaling blockade

Abstract: Background Podocytes have become a crucial target for interventions in proteinuric kidney diseases. Many studies have reported that overexpression of transient receptor potential cation channel protein 6 (TRPC6) in podocyte injury upregulates intracellular Ca2+ influx and stimulates Ca2+-dependent protease calpain-1 signaling. The traditional Chinese drug, tetrandrine, a nonselective Ca2+ channel blocker, has long been used to treat chronic kidney disease. This research aimed to explore the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…In clinics, Tet is widely applied for the therapy of lung fibrosis, rheumatoid arthritis, silicosis, and cardiovascular disease in the Chinese population ( Cheng et al, 2021 ). A previous study has also indicated that 10 μM Tet does not affect the viability of MPC5 podocytes ( Ding et al, 2021b ). In addition, preincubation with 20 μM Tet slightly reduced the viability of HaCaT human keratinocyte cells ( Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In clinics, Tet is widely applied for the therapy of lung fibrosis, rheumatoid arthritis, silicosis, and cardiovascular disease in the Chinese population ( Cheng et al, 2021 ). A previous study has also indicated that 10 μM Tet does not affect the viability of MPC5 podocytes ( Ding et al, 2021b ). In addition, preincubation with 20 μM Tet slightly reduced the viability of HaCaT human keratinocyte cells ( Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 84%
“…Tet is characterized by anti-allergenic and anti-inflammatory properties ( Ding et al, 2021b ). The anticancer effects of TetC have been reported in previous studies ( Yu et al, 2019 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that TRPC6-mediated Ca 2+ influx activates cytoplasmic calpain-1 in podocytes ( Verheijden et al, 2018 ; Ding et al, 2021 ). To investigate the effect of calpain-1 on TRPC6 mediating mitochondrial fission in HG-stimulated podocytes, we first measured the activity of calpain in podocytes respectively transfected with siTRPC6 and treated with 2-APB in HG conditions, and found that TRPC6 inhibition decreased the activity of calpain in HG-treated podocytes ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…After modeling, rats in Tet-LD, Tet-MD, Tet-HD, and CsA groups were given 4 mg/kg/d Tet (Sigma-Aldrich, USA), 8 mg/kg/d Tet, 16 mg/kg/d Tet, and 30 mg/kg/d CsA (Sigma-Aldrich) by gavage, respectively. The dosages of Tet and CsA used in this study were based on our previous report [ 27 ]. Rats in the control and ADRIA groups received the same volume of distilled water.…”
Section: Methodsmentioning
confidence: 99%